Nutritional Properties and Antinutritional Factors of Corn Paste (Kutukutu) Fermented by Different Strains of Lactic Acid Bacteria - Tchikoua Roger; Tatsadjieu Ngouné Léopold; Mbofung Carl Moses Funtong (International Journal of Food Science)
The aim of this study is to reduce antinutritional factors and to improve the nutritional properties of Kutukutu during fermentation with Lactic Acid Bacteria (LAB). For that, Kutukutu (700 g) was prepared in the laboratory and inoculated with pure cultures of LAB (109 CFU/mL). Then, preparation was incubated for 120 h. Every 24 h, Kutukutu were collected, dried at 45°C for 24 h, and analyzed. The results showed that Lactobacillus brevis G25 increased reducing sugars content to 80.7% in Kutukutu after 96 h of fermentation. Lactobacillus fermentum N33 reduced the starch content to 73.2%, while Lactobacillus brevis G11, L. brevis G25, and Lactobacillus cellobiosus M41 rather increased the protein content to 18.9%. The bioavailability of Mg and Fe increased, respectively, to 50.5% and 70.6% in the Kutukutu fermented with L. brevis G25. L. plantarum A6 reduced the tannin content to 98.8% and L. buchneri M11 reduced the phytate content to 95.5%. The principal component analysis (PCA) shows that, for a best reduction of antinutrients factors and improvement of protein content and minerals, Kutukutu must be fermented by L. brevis G25 and L. fermentum N33, respectively. These starter cultures could be used to ameliorate nutritional proprieties of Kutukutu during the fermentation.